Склад та зміни трьох геміклональних популяційних систем зелених жаб НПП «Гомільшанські ліси» - Біляєв, І.; Бондаренко, Г.; Гарбуз, Д.; Дрогваленко, М.; Сєрватовська, Л.; Сударенко, Ю.; Тепленко, Ю.; Федорова, А.; Шабанов, Д. (Матеріали наукової конференції «Стан і біорізноманіття екосистем Шацького національного природного парку та інших природоохоронних територій», смт Шацьк, 13–16 вересня 2018 р. – Львів : СПОЛОМ, 2018., 2018)
Three R-E-Ep-HPS of Siverskyi Donets center of Pelophylax esculentus complex diversity have been studied. Each system has specific features of composition and dynamics. HPS of the Iskov pond approximates to E-HPS; HPS of the Koryakiv Ravine’s pond and the Lower Dobrytskyi pond belong to E-Ep-HPS. HPS number of the Iskiv pond’s HPS is evaluated as 374±143, and for the Lower Dobrytskiy pond – 1264±619 individuals.
Keywords: Геміклональні популяційні системи; Моніторінг; Зелені жаби; Pelophylax esculentus